Development and characterisation of a Y2Ti2O7-based glass-ceramic as a potential oxidation protective coating for titanium suboxide (TiOx). Issue 14 (15th July 2021) - D'Isanto, Fabiana; Smeacetto, Federico; Martin, Hans-Peter; Sedlák, Richard; Lisnichuk, Maksym; Chrysanthou, Andreas; Salvo, Milena
Abstract: A silica-based glass-ceramic, with Y2 Ti2 O7 as the major crystalline phase, is designed, characterised and tested as an oxidation-protective coating for a titanium suboxide (TiOx ) thermoelectric material at temperatures of up to 600 °C. The optimised sinter-crystallisation treatment temperatures are found to be 1300 °C and 855 °C for a duration of 30 min, and this treatment leads to a glass-ceramic with cubic Y2 Ti2 O7 and CaAl2 Si2 O8 as crystalline phases. An increase of ~270 °C in the dilatometric softening temperature is observed after devitrification of the parent glass, thus further extending its working temperature range. Excellent adhesion of the glass-ceramic coating to the thermoelectric material is maintained after exposure to a temperature of 600 °C for 120 h under oxidising conditions, thus confirming the effectiveness of the T1 glass-ceramic in protecting the TiOx material.